1998
DOI: 10.1101/gad.12.6.806
|View full text |Cite
|
Sign up to set email alerts
|

Essential contribution of caspase 3/CPP32 to apoptosis and its associated nuclear changes

Abstract: Caspases are fundamental components of the mammalian apoptotic machinery, but the precise contribution of individual caspases is controversial. CPP32 (caspase 3) is a prototypical caspase that becomes activated during apoptosis. In this study, we took a comprehensive approach to examining the role of CPP32 in apoptosis using mice, embryonic stem (ES) cells, and mouse embryonic fibroblasts (MEFs) deficient for CPP32. CPP32 ex3−/− mice have reduced viability and, consistent with an earlier report, display defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
557
8
7

Year Published

1999
1999
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 786 publications
(606 citation statements)
references
References 58 publications
34
557
8
7
Order By: Relevance
“…In contrast, TGFb-mediated-nuclear fragmentation was reproducibly inhibited to approximately the same extent by ZVAD-fmk and DEVD-fmk. This strongly suggests that the nuclear fragmentation observed during TGFbmediated apoptosis is more directly under the control of caspase-3 as it has been reported in other experimental systems (Janicke et al, 1998;Shiokawa et al, 1997;Toyoshima et al, 1997;Woo et al, 1998).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In contrast, TGFb-mediated-nuclear fragmentation was reproducibly inhibited to approximately the same extent by ZVAD-fmk and DEVD-fmk. This strongly suggests that the nuclear fragmentation observed during TGFbmediated apoptosis is more directly under the control of caspase-3 as it has been reported in other experimental systems (Janicke et al, 1998;Shiokawa et al, 1997;Toyoshima et al, 1997;Woo et al, 1998).…”
Section: Discussionsupporting
confidence: 74%
“…The remaining cleavage of PARP in DEVD pre-treated cells was probably due to caspases other than caspase-3 also being able to BL41 cells (0.5 10 6 /ml) were cultured for 72 h without (control) or in the presence of TGFb (1 ng/ml) alone or with ZVAD-fmk (100 mM) or the combination of TGFb and ZVAD-fmk. Total number and per cent of viable cells were quanti®ed by counting of trypan blue excluding cells cleave PARP in vivo albeit with a lower e ciency (Patel et al, 1996;Woo et al, 1998). We therefore used this concentration to study the involvement of caspase-3 during TGFb-mediated apoptosis.…”
Section: Tgfb-mediated Nuclear Fragmentation Is Abolished By Devd-fmkmentioning
confidence: 99%
“…The defect in the execution of apoptotic cell death was caused by the failure to initiate JNK-induced cytochrome c release from the mitochondria [204]. This malfunction is significant since it is critical for the subsequent sequential activation of Apaf-1 [120], the initiator-caspase caspase-9 [76] and finally the effector-caspase caspase-3 [217] all of which are essential in the execution of apoptosis. Tournier et al [204] suggested that the apoptotic response is suppressed in JNK null MEF due to the absence of JNK, which is needed to initiate the apoptotic cascade (Fig.…”
Section: Map Kinase Signalingmentioning
confidence: 99%
“…B6 mice were ordered from Jackson Laboratories (Bar Harbor, ME) whereas pko mice on the B6 background were bred in the animal colony from stock provided by Dr. H. Hentgartner [42]. Caspase 3 -/-mice and heterozygous littermates [24] and caspase 9 -/-/RAG2 -/-and wild-type/RAG2 -/-chimeras [29] were generated as described.…”
Section: Animalsmentioning
confidence: 99%
“…Other apoptotic events act through compromise of mitochondrial activity and lead to activation of caspase 9 (reviewed in [21,22]). Both receptor-mediated and mitochondrial pathways converge upon caspase 3 [23,24], which causes DNA fragmentation through degradation of a DNase inhibitor (ICAD) and release of a caspase-activated DNase [25][26][27].…”
Section: Introductionmentioning
confidence: 99%